Percutaneous hollow nail internal fixation treatment for fractures of the pubic symphysis and its adjacent areas - Ping, Zhang (Frontiers in Surgery, 2024)
PurposeTo explore the percutaneous minimally invasive treatment of pubic symphysis and its adjacent fractures.MethodSince May 2021, 13 cases of fractures involving the pubic symphysis and its adjacent parts were treated with x-ray fluoroscopic localization and percutaneous cannulated screw fixation across the symphysis pubis, the guide pin pierced the symphysis pubis and the fracture end and stopped at the inner edge of the acetabulum. Visual analogue scale (VAS) was used to evaluate the effect of the operation, and the patients were followed up.ResultThe screw insertion operation time was 25–40 min, with an average of 31.45 min; The number of perspectives is 20–40, with an average of 28.75. The average intraoperative blood loss was 10 ml, and there were no puncture complications such as nerve or vascular damage. The initial stability of the fractured end of the patient after surgery was good. The VAS score decreased from preoperative 8–10 points to postoperative 1–2 points (average of 1.5 points). The follow-up time was 3–25 months, with an average of 8.5 months. At the last follow-up, the excellent and good rate of pelvic function according to Majeed pelvic function scoring system was 100%. One patient had screws removed 1.5 years after surgery, while the remaining twelve patients did not have screws removed. All patients did not experience any discomfort symptoms caused by pubic symphysis fixation.ConclusionPercutaneous hollow nail internal fixation is an effective method for treating fractures of the pubic symphysis and its adjacent parts.